Co-infection of Cytomegalovirus and Epstein-Barr Virus Diminishes the Frequency of CD56dimNKG2A+KIR− NK Cells and Contributes to Suboptimal Control of EBV in Immunosuppressed Children With Post-transplant Lymphoproliferative Disorder - Lam, Janice K. P.; Azzi, Tarik; Hui, K. F.; Wong, Aikha M. G.; McHugh, Donal; Caduff, Nicole; Chan, K. H.; Münz, Christian; Chiang, Alan K. S. (Frontiers in Immunology, 2020)
Post-transplant lymphoproliferative disorder (PTLD) is a rare but potentially life-threatening complication, frequently associated with Epstein-Barr virus (EBV), which develops after solid organ or stem cell transplantation. Immunosuppression received by transplant recipients has a significant impact on the development of PTLD by suppressing the function of T cells. The preferential proliferation of NKG2A-positive natural killer (NK) cells during primary symptomatic EBV infection known as infectious mononucleosis (IM) and their reactivity towards EBV-infected B cells point to a role of NK cell in the immune control of EBV. However, NK cell-mediated immune response to EBV in immunosuppressed transplant recipients who develop PTLD remains unclear. In this study, we longitudinally analyzed the phenotype and function of different NK cell subsets in a cohort of pediatric liver transplant patients who develop PTLD and compared them to those of children with IM. We found persistently elevated plasma EBV DNA levels in the PTLD patients indicating suboptimal anti-viral immune control. PTLD patients had markedly decreased frequency of CD56dimNKG2A+Killer Immunoglobulin-like receptor (KIR)- NK cells from the time of diagnosis through remission compared to those of IM patients. Whilst the proliferation of CD56dimNKG2A+KIR- NK cells was diminished in PTLD patients, this NK cell subset maintained its ability to potently degranulate against EBV-infected B cells. Compared to cytomegalovirus (CMV)-seropositive and -negative IM patients, PTLD patients co-infected with CMV and EBV had significantly higher levels of a CMV-associated CD56dimNKG2ChiCD57+NKG2A-KIR+ NK cell subset accumulating at the expense of NKG2A+KIR- NK cells. Taken together, our data indicate that co-infection of CMV and EBV diminishes the frequency of CD56dimNKG2A+KIR- NK cells and contributes to suboptimal control of EBV in immunosuppressed children with PTLD.